Improving the Quality of Learning for Students, Governance and Office Automation at SMKN 3 Jeneponto Regency - Sailan, Manan; Arhas, Sitti Hardiyanti; Hasan, Muhammad Nurul Hakim; Darwis, Muh. (Jurnal Office, 2023)
Education is a learning process involving teaching staff and students which aims to produce quality and competitive students. This research aims to improve the learning system which still uses old patterns in order to improve the quality of learning for students with management and office automation. Education in Indonesia cannot yet compete in the world because the Indonesian education system and quality has not produced many intellectual generations. Therefore, to create good and quality education, teaching staff must be able to provide quality learning to students at school. In the world of education, the role of teachers is very important. This research is qualitative in nature, therefore, to achieve the research objectives, data collection techniques were used, namely interviews, observation and documentation. The results of the research show that improving the quality of learning for students as educators' learning behavior provides a sense of comfort and teachers become role models for students at school. Student behavior or activities enable students to develop their talents and make them confident. The latest thing from this research is that teachers have implemented innovative and creative learning that is different from previous learning and the school has also made new breakthroughs to improve the quality of learning in schools by adding supporting tools to the learning process.